Initial consonant cluster epenthesis in Turkish and its implications to EFL - Namık Ülkersoy; Bilal Genç; Volkan Darmaz (Ömer Gökhan Ulum, 2021)
Abstract The phonological structure of Turkish does not allow word-initial consonant clusters. That is, the syllable onset position of borrowed vocabulary requires the insertion of an epenthetic high vowel. This changes the syllable structure by the addition of an extra syllable to the word. In Turkish schools, all grammar teachers teach those borrowed words as if they were one syllable words. However, the situation is different phonologically since these are not one syllable but two syllable words. Borrowed words such as tren (English train), plan (English plan) are pronounced with the insertion of the high vowel [i] and therefore become two syllable words. Our goal in this paper was to analyse such borrowed words drawing syllable diagrams in order to prove that these loan words actually consist of two syllables in Turkish. The diagrams were illustrated in phonetic transcription. We also concluded that Turkish initial consonant cluster epenthesis might affect Turkish EFL learners' pronunciation of English words in their foreign language classes. Key words: epenthesis, consonant clusters, onset, Turkish.